2014
DOI: 10.1037/a0037450
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety sensitivity mediates relations between emotional disorders and smoking.

Abstract: Objectives Research has documented consistent and robust relations between emotional disorders (i.e., depressive and anxiety disorders) and smoking. Yet, it is presently unclear whether anxiety sensitivity, the fear of aversive internal anxiety states, may account for the relations between emotional disorders and various smoking processes, including nicotine dependence, perceived barriers to smoking cessation, and severity of problematic symptoms while quitting during past cessation attempts. Method Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 61 publications
2
26
0
Order By: Relevance
“…In the first model, we tested whether individuals presenting with high anxiety sensitivity assigned to the ST+EX condition reported lower anxiety sensitivity during the targeted quit week relative to their counterparts assigned to the ST+CTRL condition. This hypothesis is consistent with our previous work guiding the current study showing that exercise effectively reduces anxiety sensitivity (3, 1416) and lower anxiety sensitivity is associated with greater odds of quit success (1113). Accordingly, we modeled the growth curve of ASI scores from week 0 through quit week using multilevel modeling (MLM) with Time (in weeks), Treatment Condition, and Time × Treatment Condition as predictors.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…In the first model, we tested whether individuals presenting with high anxiety sensitivity assigned to the ST+EX condition reported lower anxiety sensitivity during the targeted quit week relative to their counterparts assigned to the ST+CTRL condition. This hypothesis is consistent with our previous work guiding the current study showing that exercise effectively reduces anxiety sensitivity (3, 1416) and lower anxiety sensitivity is associated with greater odds of quit success (1113). Accordingly, we modeled the growth curve of ASI scores from week 0 through quit week using multilevel modeling (MLM) with Time (in weeks), Treatment Condition, and Time × Treatment Condition as predictors.…”
Section: Resultssupporting
confidence: 94%
“…This analysis showed that, in the ST+CTRL condition, participants with higher ASI had lower abstinence rates ( b =−.07, SE= .025, t (1171)=2.95, p =.003 for PPA; and b =−.08, SE= .016, t (993)=5.35, p <.001 for PA). These effects replicate earlier findings that smokers with high anxiety sensitivity are less likely to successfully quit smoking than those with low anxiety sensitivity (1113). On the other hand, in the ST+EX condition ASI scores were not significantly related to abstinence as measured by PPA ( b =−.02, SE= .023, t (1171)=−0.76, p =.447), and was only weakly related to prolonged abstinence ( b =−.03, SE= .014, t (993)=−1.97, p =.049).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, AS may prevent regular smokers from making a cessation attempt. Consistent with this perspective, Zvolensky, Farris, Schmidt, and Smits (in press) recently found in treatment-seeking daily smokers that AS was indirectly related (i.e., statistical mediation) to greater perceived barriers to cessation, greater number of prior quit attempts, and greater mood-management smoking expectancies through the the tendency to escape and avoid aversive smoking-related thoughts, feelings and internal sensations. Because high-AS individuals may be more apt to excessively worry about the stress of quitting because they inflexibly rely on smoking to cope with anxiety, they may be at risk for treatment drop out.…”
Section: Trandiagnostic Emotional Vulnerabilities and Smokingmentioning
confidence: 79%
“…Results are mixed on this issue, with a wide range of effect sizes for relations of AS to cig/day and nicotine dependence severity in daily smokers ( r s = .03 to .44; Johnson et al, 2012; Zvolensky, Farris, Schmidt, & Smits, in press; Zvolensky, Kotov, et al, 2003). Given the methodological caveats with these studies (e.g., cross-sectional, do not assess progression from non-daily to daily smoking), prospective work is warranted to clarify if AS accelerates progression from irregular to regular smoking.…”
Section: Trandiagnostic Emotional Vulnerabilities and Smokingmentioning
confidence: 99%